The Impact of Plasmid-Mediated Genes on the Virulence of Salmonella Enterica in Human Infections - Bakir, Wasan Abdul- elah; Ahmed, Entisar Manfi; Shalash, Seror Ali Abdul Hussein (American Journal of Biology and Natural Sciences, 2025)
Salmonella enterica is a significant pathogen responsible for a wide range of human infections, including gastroenteritis, typhoid fever, and septicemia. One of the key factors contributing to its pathogenicity is the acquisition of virulence-associated genes carried on plasmids. These extrachromosomal genetic elements play a crucial role in enhancing the bacterium's ability to invade host cells, evade immune responses, and establish persistent infections. Plasmid-mediated genes encode for various virulence determinants such as toxins, adhesins, and secretion systems, most notably the type III secretion system (T3SS), which facilitates the translocation of effector proteins into host cells. Furthermore, certain plasmids also carry antibiotic resistance genes, which complicate treatment and increase the severity and duration of infections. This review explores the molecular mechanisms by which plasmid-borne genes influence the virulence of S. enterica, with a focus on the IncF and IncI plasmid families known to harbor key virulence and resistance genes. Understanding the dynamics of plasmid acquisition and expression provides insight into the evolution of highly virulent and multidrug-resistant strains. It also highlights the need for ongoing surveillance and genomic studies to monitor the spread of such plasmids in clinical and environmental settings. Ultimately, targeting plasmid-encoded virulence factors may offer new strategies for combating Salmonella infections, especially in the context of rising antibiotic resistance. This study underscores the importance of plasmid-mediated gene transfer in shaping the pathogenic potential of S. enterica and its implications for public health and clinical management.